Taphonomy and ontogeny of the brachyuran crab Exucarcinus gonzagai, from the Lower Cretaceous (Aptian) Romualdo Formation, Araripe Basin, NE Brazil - Matos, Suzana Aparecida [UNESP]; Castilho, Antonio Leão [UNESP]; Prado, Ludmila Alves Cadeira do; Bondioli, João Guedes; Varejão, Filipe Giovanini; Custódio, Michele Andriolli; Fürsich, Franz Theodor; Assine, Mario Luis [UNESP]; Simões, Marcello Guimarães [UNESP] (Elsevier, 2021)
Brachyurans played important ecological and evolutionary roles in the marine benthic communities of the past and were the components of the Mesozoic Decapod Revolution. Therefore, the search for their fossil remains is fundamental to understanding the composition, diversity, and ecological structure of Mesozoic marine benthic communities. Brachyuran remains are uncommon in the decapod record of the Aptian Romualdo Formation in the Araripe Basin. In this context, we recorded and described new occurrences of Exucarcinus gonzagai, preserved in shales from the middle portion of the Romualdo Formation, near the city of Jardim in the State of Ceará. Comparisons between these new specimens and former specimens from the Exu locality, State of Pernambuco, including the type material, allowed us to recognize, for the first time, three distinct ontogenetic stages (i.e., informally referred as I, II, and III). Throughout ontogenetic development, the carapace becomes wider and spinier. Stage III carapaces exhibit a large number of grooves, although the grooves are poorly impressed, and some are pitted. Growth also resulted in better-developed orbital lobes and fissures. In addition, the preservation of some anatomical structures is highly influenced by the carapace fossilization process (i.e., molds or cuticles), including the tubercles, grooves, and spines. Unfortunately, those characters that can vary according to ontogenetic development or fossilization are commonly used in the systematic and phylogenetic decisions of the group. Hence, it is advisable to consider these changes whenever possible to avoid the erection of taphotaxons and mistaken phylogenetic decisions.
Keywords: Aptian; Brachyura; Exucarcinus; Frog crab; Orithopsidae; Romualdo formation